2017
DOI: 10.1177/1071100717698695
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Scandinavian Total Ankle Replacement

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…The mobile-bearing HINTEGRA (Newdeal, Lyon, France/Integra) and Scandinavian Total Ankle Replacement (STAR; Waldemar Link, Hamburg, Germany) prostheses have been reported to have failure rates of 6% to 8% at 5 years. 3,8,17 The INBONE II (Wright Medical Technology) prosthesis has been reported to have a 3% failure rate at 2 years. 19 The older INBONE I (Wright Medical Technology) prosthesis has a reported failure rate of less than 10% with a minimum 4-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The mobile-bearing HINTEGRA (Newdeal, Lyon, France/Integra) and Scandinavian Total Ankle Replacement (STAR; Waldemar Link, Hamburg, Germany) prostheses have been reported to have failure rates of 6% to 8% at 5 years. 3,8,17 The INBONE II (Wright Medical Technology) prosthesis has been reported to have a 3% failure rate at 2 years. 19 The older INBONE I (Wright Medical Technology) prosthesis has a reported failure rate of less than 10% with a minimum 4-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Uncemented, 3-component total ankle replacements (TAR) have shown promising but somewhat varying results in medium-and long-term reports (Wood and Deakin 2003, Fevang et al 2007, Skytta et al 2010, Bonnin et al 2011, Henricson et al 2011b, Mann et al 2011, Tomlinson and Harrison 2012, Barg et al 2013, Zaidi et al 2013, Henricson and Carlsson 2015, Kerkhoff et al 2016, Frigg et al 2017, Palanca et al 2018, Clough et al 2019. Some evidence points to better results with modern prosthetic designs (Barg et al 2015, Koivu et al 2017a, Clough et al 2019. National registries give better insight into current real-world results, including more patients and different surgeons, than data from single surgeons or institutions.…”
mentioning
confidence: 99%
“…This is better than the results described by Henricsson et al [ 13 ], that is, 78% survival at 5 years. One study found a 94% implant survival at 5 years, even 87% survival at 10 years, which dropped quite steep to 64% after 15 years [ 30 ]. One of our exclusion criteria for a TAR is age: we excluded patients younger than 65 years, in whom we prefer an arthrodesis, except for rheumatoid patients.…”
Section: Discussionmentioning
confidence: 99%